2002
DOI: 10.1016/s0735-1097(02)01989-7
|View full text |Cite
|
Sign up to set email alerts
|

In-stent restenosis in small coronary arteries

Abstract: This study supports that strut thickness is an independent predictor of restenosis in coronary arteries with a reference diameter of 2.75 to 2.99 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
123
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(138 citation statements)
references
References 19 publications
10
123
1
4
Order By: Relevance
“…This may be incorrect as there is evidence that newer stent designs with thinner struts may have lower restenosis rates than older stents. 95,96 In one retrospective study, the stent design was the second most important factor in predicting restenosis after lesion type, and different stents had restenosis rates of between 20 and 50%. 97 There are also other ways in which technology differed or has changed -in particular the adjuvant drug therapies may differ substantially between those early studies that used aspirin, heparin, ticlopidine or clopidogrel, or the much more recent studies which have used the glycoprotein IIb/IIIa receptor antagonists.…”
Section: Comparability Of Interventionsmentioning
confidence: 99%
“…This may be incorrect as there is evidence that newer stent designs with thinner struts may have lower restenosis rates than older stents. 95,96 In one retrospective study, the stent design was the second most important factor in predicting restenosis after lesion type, and different stents had restenosis rates of between 20 and 50%. 97 There are also other ways in which technology differed or has changed -in particular the adjuvant drug therapies may differ substantially between those early studies that used aspirin, heparin, ticlopidine or clopidogrel, or the much more recent studies which have used the glycoprotein IIb/IIIa receptor antagonists.…”
Section: Comparability Of Interventionsmentioning
confidence: 99%
“…In recent years, several clinical trials have identified stent strut thickness as an independent predictor of restenosis [2,12,23]. A clear conclusion from the many clinical studies on stent strut thickness is that stents with thinner struts have a lower restenosis rate, consequently, most of the current generation of stents are produced with thinner struts using high strength materials such as cobalt-chromium alloys [20].…”
Section: Introductionmentioning
confidence: 99%
“…The strut thickness has been shown to be an important determinant of the long-term restenosis rate. [1][2][3][4] This prospective, nonrandomized, multicenter study was designed to assess the safety and efficacy of the Medtronic Driver stent.• • • Patients with clinical evidence of stable or unstable angina pectoris, or positive functional study findings, with a planned percutaneous transluminal coronary angioplasty procedure of a single de novo lesion in a native coronary artery were considered for inclusion. Lesions (Յ13 mm) situated in a major coronary artery or major branch with estimated stenosis of 50% to 100% and a diameter suitable for implantation of a single stent with a diameter of 3.0 to 4.0 mm were considered eligible for enrollment.…”
mentioning
confidence: 99%
“…The strut thickness has been shown to be an important determinant of the long-term restenosis rate. [1][2][3][4] This prospective, nonrandomized, multicenter study was designed to assess the safety and efficacy of the Medtronic Driver stent.…”
mentioning
confidence: 99%